THE VALIDITY OF THE ENVIRONMENTAL KUZNETS CURVE IN FOREIGN TRADE: FOURIER BOOTSTRAP AARDL ANALYSIS FOR E7 COUNTRIES (Third Sector Social Economic Review, 2024)
It is useful to analyze the factors polluting the livable environment, whose sustainability and protection are of vital importance to all living things, and to take the necessary precautions promptly. Within this scope, the effects of foreign trade and foreign direct investments (FDI) on environmental pollution in BRICMT countries, one of the fastest developing economies of recent times, were analyzed with the Fourier KPSS stationarity test, Fourier Bootstrap AARDL method, and Fourier Bootstrap Toda-Yamamoto causality test for the period 1980-2021 in this study. According to the findings, since increasing exports and FDI in China increase environmental pollution both in the short term and the long term, the Pollution Haven Hypothesis (PHH) is valid. While environmental pollution increased in China, Brazil, Mexico, and Turkey with increasing imports, it decreased in Russia. The short-term impact of imports on rising environmental contamination is also valid for Brazil. Since FDI increases environmental pollution in the long run in Brazil and Mexico, the PHH is valid in these countries. In Russia and Mexico, where there are findings that FDI reduces environmental pollution in the short term, the Pollution Halo Hypothesis (KHH) is valid in the short termin these countries. According to the Fourier Bootstrap Toda-Yamamoto causality test results, it was determined that there are causal relationships between exports and imports and environmental pollution in China and India, and between FDI and environmental pollution in Russia and Brazil.
Keywords: Foreign Trade; Cubic Environmental Kuznets Curve; Fourier Bootstrap AARDL Method